Handbook of Research on Electronic Surveys and Measurements 2007
DOI: 10.4018/978-1-59140-792-8.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode Electronic Survey Lessons and Experiences

Abstract: This paper presents a number of insights gained from a dual-mode survey of software designers recently conducted in Ireland. It describes the sampling method, pilot test procedures, response patterns, and the mechanisms engaged to authenticate partipants and to filter duplicate responses. An outline is also given of how various factors with potentially beneficial affects on response rates were considered, as well as a breakdown of costs. Finally, the paper concludes with a summary of the main lessons learned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies have found little change in response rates when web follows mail first (Dillman et al, 2014). However, significant increases in response were reported in studies where the web survey mode was first, followed by mail (Dillman et al, 2014;Lang, 2007;Messer & Dillman, 2011;Millar & Dillman, 2011). Concerning timing of mode switch, Wagner et al (2017) found no significant difference in response rates when switching modes after the first, second, third, and fourth contact leading to the recommendation of switching at the final contact to the more expensive mode.…”
Section: Review Of Literaturementioning
confidence: 96%
“…Studies have found little change in response rates when web follows mail first (Dillman et al, 2014). However, significant increases in response were reported in studies where the web survey mode was first, followed by mail (Dillman et al, 2014;Lang, 2007;Messer & Dillman, 2011;Millar & Dillman, 2011). Concerning timing of mode switch, Wagner et al (2017) found no significant difference in response rates when switching modes after the first, second, third, and fourth contact leading to the recommendation of switching at the final contact to the more expensive mode.…”
Section: Review Of Literaturementioning
confidence: 96%
“…This part of the survey is called the name interpreter (Snijders, 1999 : 29). The literature recommends keeping self-administered online surveys short to prevent respondents from dropping out due to interview fatigue (Lang, 2007 : 71). The number of questions to be answered in the name interpreter is multiplied by the number of individuals mentioned.…”
Section: Empirical Strategymentioning
confidence: 99%